Weakened Mannheim Curves in Pseudo-Galilean 3-Space: Murat Kemal Karacan, Yılmaz Tunçer - Team, Support (Thai Journal of Mathematics, 2017)
In this study, Frenet-Mannheim curves and Weakened Mannheim curves are investigated in Pseudo-Galilean 3-space. Some characterizations for this curves are obtained.